Evaluation of Four Tomato Genotypes Resistance to Root-Knot Nematode - Faraj, Nask Mohamad; A. Qadir, Rebin (Kurdistan Journal of Applied Research, 2018)
The root-knot nematode incited by Meloidogyne incognita is one of the top diseases affecting tomato production worldwide. Nematicides can be effectively used to control the disease, but is costly and harmful to human life and environmental pollution. Alternatively resistant cultivars can be used inexpensive and eco-friendly. Resistance evaluation of five tomato cultivars (Red Rock, King Rock, Presto F1, Super Queen and Super Regina) were tested using randomized complete block design with five replications and three nematode inoculums (0, 500 and 1500 egg/second juvenile per pot). The statistical analysis gave significant differences among the genotypes, nematode densities level with their interactions. Among genotypes, Red Rock recorded significantly highest plant height (57.0) cm, Presto F1 (37.8) cm, King Rock (35.2) cm, Super Regina (30.1) cm and Super queen showed lowest (25.4) cm. As an alternative for managing the nematodes, further experiments are required in the field for applying plant resistances.